MAJOR CAUSES OF ORGAN AND CARCASS CONDEMNATIONS OF CATTLE AND THEIR ASSOCIATED FINANCIAL LOSS AT THE TAMALE ABATTOIR, GHANA - Mohammed, A.; Abdulai, A.; Birteeb, P. T.; Husssein, S. M. A. (UDS International Journal of Development, 2018)
A cross-sectional study was conducted from January to December, 2016 to identify the major causes of carcass and organ condemnation, sources of cattle with disease incidence and to estimate direct economic losses due to carcass and organ condemnation at the Tamale Abattoir. Post-mortem examination was used to identify the gross pathological changes. The study revealed that, out of 13725 cattle slaughtered, 276 (2%) had various disease conditions that resulted in the condemnation of the carcass or organ. There was an association between months of the year and diseases incidence, as the Cramers V value was significant (V = 0.68, P < 0.001, df =11). One whole carcass (0.007%) was condemned due to Lumpy Skin Disease (LSD) with 376 organs condemned. Tuberculosis (TB) caused the highest number of organ condemnation with 40.63%, followed by Contagious Bovine Pleuropneumonia (CBPP) (28.53%), Abscesses (10.66%), Fracture (5.19%), Enteritis (3.75%), LSD (2.6%), Mange (1.7%), Mastitis (1.7%), Jaundice (1.15%) and gangrene (1.15%). Majority (29%) of cattle with ill-health conditions were from the Gushegu District, followed by Tamale metropolis (21%), Savelugu (16.7%), Karaga (6.9%) North Gonja (6.9%), Mion (6.5%) and East Gonja (4.3%). The rest were Tolon (3.3%), Kumbungu (1.8%), Central Gonja (1.4%), Yendi municipal (3%), West Mamprusi (0.72%) and East Mamprusi (0.4%). Based on the results of source of cattle and diseases incidence, the Cramers V value of the Chi-square goodness – of – fit was not significant (V = 0.247, P = 0.103, df =210). The total direct economic loss due to organ and carcass condemnation was GHc14, 955.00 for 2016 period. It was concluded that TB and CBPP caused the highest number of organs condemned resulting in financial loss to the Tamale abattoir. Keywords: Cattle, Animal Diseases, Carcass and Organ Condemnation, Abattoir